Rowell syndrome with recurrence from photoexacerbation: A case report. (April 2019) - Alkul, Suzanne; Behrens, Emily; Stetson, Cloyce
Rowell syndrome is a controversial entity composed of erythema multiforme-like lesions coexisting with lupus erythematosus. We describe a case of a 61-year-old male with a history of systemic lupus erythematosus who presented with photoexacerbated flaccid bullae and erosive plaques after repetitive sun exposure. Based on his clinical history, biopsy, and laboratory findings, he fulfilled diagnostic criteria for Rowell syndrome as described by Zeitouni et al. With oral prednisone, hydroxychloroquine, mycophenolate mofetil, and local wound care with petrolatum, the patient's number of lesions decreased, as well as his pain and tenderness. He subsequently did not develop any new erosions. This case highlights the diagnostic criteria of this hybrid clinicopathological syndrome and its nature of photosensitivity.